1998
DOI: 10.1016/s0378-1097(98)00008-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of antimicrobial action of indolicidin

Abstract: Indolicidin, a 13-residue antimicrobial peptide isolated from cytoplasmic granules of bovine neutrophils, exhibits activity against Gram-positive and Gram-negative bacteria as well as fungi. Although indolicidin is bactericidal and permeabilizes the bacterial membranes, it does not lyse the bacterial cells. We examined the effect of bactericidal concentrations of indolicidin on the morphology of Escherichia coli cells and found that it induces filamentation. Further investigations showed that indolicidin inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 19 publications
2
90
0
4
Order By: Relevance
“…[12,57,[59][60][61] The AMPs indolicitin and buforin II have also demonstrated the ability to bind directly to DNA. [34,62] It has been shown that wheat seed purothionin is able to block in vitro DNA synthesis through inhibition of the enzyme ribonucleotide reductase. It has been proposed that inhibition of DNA synthesis may explain the toxic effect of thionins against mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…[12,57,[59][60][61] The AMPs indolicitin and buforin II have also demonstrated the ability to bind directly to DNA. [34,62] It has been shown that wheat seed purothionin is able to block in vitro DNA synthesis through inhibition of the enzyme ribonucleotide reductase. It has been proposed that inhibition of DNA synthesis may explain the toxic effect of thionins against mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Such filamentation was reported to be the result of binding to the intracellular macromolecules including DNA (puroindoline and indolicidin), RNA polymerase (microcin J25), and ClpP protease (acyldepsipeptides). [13][14][15][16] We thus speculated that RO-A would also exhibit its antimicrobial activity by interacting with intracellular macromolecules after penetrating the cellular membrane.…”
Section: Observation Of E Coli Morphology Treated With Ro-amentioning
confidence: 99%
“…It has been reported that intracellular genomic DNA is an important target of antimicrobial peptides (13). After interacting with genomic DNAs, a number of antimicrobial peptides interrupt the expression of proteins involved in gene replication and transcription, resulting in bacterial death (28,29). In this study, the cell membrane permeabilization assay suggests that the membrane is the preliminary target of AN5-1 and AN5-1 disrupts both the outer and inner bacterial membranes.…”
Section: Discussionmentioning
confidence: 72%